Level of compliance and factors associated with non-compliance to treatment among the mentally ill patients - Lama, S; Lakshmi, K V; Shyangwa, P M; Parajuli, P (Health Renaissance, 2012)
Background: Mental illnesses are treatable and need medication and other therapies i.e. counseling, psychotherapy etc for the better outcome. Poor adherence to psychiatric medication regimens is a major obstacle to the effective care of persons who have chronic mental illness. Objectives: The study aims to identify the level of compliance and factors associated with non-compliance to treatment regimen. Methods: This was a hospital based cross sectional study carried out in psychiatric ward and OPD at B.P.Koirala Institute of Health Sciences, Dharan Nepal. A total of 150 patients were included as study samples using purposive sampling technique. Data was collected using self developed, pre tested, semi structured Pro forma by interview method. Results: Half of the patients showed average compliance. Thirty seven percentages of patients had good compliance and only 13% showed poor compliance. There was no association between drug compliance and demographic variables (p> 0.05). Drug compliance was significantly associated with factors such as drug related aspects, treatment access related factors, quality of interaction with treating team, family support, attitude towards mental illness and relatives' insight towards mental illness (p<0.05 ). Conclusion: The findings of the study highlighted the various factors such as drug related, social support, and treatment access related factors are influencing the drug compliance among the mentally ill patients. DOI: http://dx.doi.org/10.3126/hren.v10i2.6577 Health Renaissance 2012; Vol 10 (No.2); 113-117